Perancangan Sistem Pakar Gejala Penyakit Saluran Pencernaan Dengan Pengobatan Tanaman Herbal Berbasis Web - Angga Ardiansyah; Dany Pratmanto; Aep Saprul Mujahid (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Expert system is a software package or computer program package that is intended as a provider of advice and help tools in solving problems in certain areas of specialization such as medical, education, and so on. The development of the development of expert systems in the biomedical field is one thing that is expected to improve the quality of human life. One of them is by applying an expert system by using the Forward Chaining method to diagnose psychotic disorders due to substances. This study aims to increase knowledge about how to make an inference engine to control the process of identifying solutions using the Forward Chaining method, as well as designing expert system applications using the Forward Chaining method to diagnose substance-induced psychotic disorders. Keywords: Expert System Programs, Digestive Diseases, Herbal Plants